Congestion spillover effects of Chinese hub airports on international connecting traffic. Issue 2 (29th November 2019) - Zhang, Shengrun; Fuellhart, Kurt; Wang, Yanjun; Wu, Weiwei; Zhu, Jinfu; Witlox, Frank
Abstract : This paper evaluates the congestion spillover effects of the 'big three' Chinese hub airports – Beijing Capital (PEK), Shanghai Pudong (PVG), and Guangzhou Baiyun (CAN) – on international connecting traffic with 20 worldwide hubs between 2010 and 2017. We find that the spillover effects, or 'avoidance' of the major Chinese hubs, have different spatial distributions across the 'big three'. Specifically, we find that there are effects between PEK and Kuala Lumpur, Bangkok, Singapore, and Dubai; between PVG and Seoul; and between CAN and Hong Kong, Seoul, Kuala Lumpur, Helsinki and Istanbul. This modeling technique also contributes to research on hub airport classification.